Transforming Human Resource Management Practices for Generation Z in the Contemporary Workplace - Saepudin, Aep; Handayani, Sri (Research Horizon, 2026)
The workforce is shifting as Generation Z (born 1997–2012), the first true digital natives, enters workplaces with unique traits shaped by connectivity, instant information, and strong social-environmental awareness. This creates opportunities and challenges for human resource management, requiring adaptations in recruitment, development, evaluation, and culture to sustain engagement and retention. This article aims to conceptually examine how human resource management can effectively respond to the needs and expectations of Generation Z in the workplace. The study adopts a conceptual review approach, synthesizing recent scholarly literature, global reports, and empirical insights from reputable sources to explore generational dynamics and propose adaptive strategies. The findings indicate that Generation Z prioritizes meaningful work, flexibility, continuous learning, real-time feedback, inclusivity, and mental health support over traditional rewards alone. They expect technology-integrated processes, value-aligned organizations, and human-centered environments that reject rigid hierarchies. These insights imply that organizations must transform human resource management into a strategic, agile function focused on authenticity, digital enablement, and employee well-being. Successful adaptation can lead to higher engagement, stronger retention of young talent, and enhanced innovation, while failure to evolve risks increased turnover and reduced competitiveness in attracting the next generation of workers.